Antiseizure medication and perceived "fair" cost allocation: A factorial survey among neurologists, persons with epilepsy, their relatives, and a control group. Issue 10 (7th August 2022) - Stritzelberger, Jenny; Walther, Katrin; Olmes, David; Gollwitzer, Stefanie; Graf, Wolfgang; Welte, Tamara M.; Lang, Johannes D.; Reindl, Caroline; Schwab, Stefan; Kriwy, Peter; Hamer, Hajo M.
Abstract: Objective: Because resources are limited in modern health care systems, the decision on the allocation of expensive drugs can be supported by a public consent. This study examines how various factors influence subjectively perceived "fair" pricing of antiseizure medication (ASM) among four groups including physicians, persons with epilepsy (PWEs), their relatives, and a control group. Methods: We conducted a factorial survey. Vignettes featured a fictional PWE receiving a fictional ASM. The characteristics of the fictional PWE, ASM, and epilepsy varied. Participants were asked to assess the subjectively appropriate annual cost of ASM treatment per year for each scenario. Results: Fifty‐seven PWEs (mean age (SD) 37.7 ± 12.3, 45.6% female), 44 relatives (age 48.4 ± 15.7, 51.1% female), 46 neurologists (age 37.1 ± 9.6, 65.2% female), and 47 persons in the control group (age 31.2 ± 11.2, 68.1% female) completed the questionnaire. The amount of money that respondents were willing to spend for ASM treatment was higher than currently needed in Germany and increased with disease severity among all groups. All groups except for PWEs accepted higher costs of a drug with better seizure control. Physicians and the control group, but not PWEs and their relatives, tended to do so also for minor or no side effects. Physicians reduced the costs for unemployed patients and the control group spent less money for older patients. Significance: ASM effectiveness appears to justify higher costs. However, the control group attributed less money to older PWEs and physicians allocated fewer drug costs to unemployed PWEs.